Five decades of research on the development of eutectic as engineering materials. (January 2022) - Tiwary, Chandra Sekhar; Pandey, Prafull; Sarkar, Suman; Das, Rakesh; Samal, Sumanta; Biswas, Krishanu; Chattopadhyay, Kamanio
Abstract: We present a brief review and perspective on the development of eutectic alloys, emphasizing the emergence of complex microstructures during eutectic solidification of ternary and higher-order multicomponent alloys. Such alloys' abundant existence promises a large domain in the alloy development space for newer materials suitable for high-temperature applications. Hence the review explores these developments in eutectic alloys based on aluminum, titanium, nickel, intermetallics, and recently developed high entropy alloys. While the importance of fundamental understanding and various functional properties of the eutectic alloys cannot be ignored, this paper focuses primarily on the microstructure and their mechanical properties. The possibilities of ultrafine eutectics and multiscale variation of length scale and morphologies are emphasized. It highlights the potential for the future emergence of these alloys as high-strength structural materials for engineering applications.